Enhancing HOTS using Problem-Based Learning and Digital Game in the Context of Malaysian Primary School - Chuang Tong, Liew; Rosli, Mohd Shafie; Saleh, Nor Shela (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Learning in the 21st century emphasize on development of higher order thinking skills such as problem-solving skills with substantial highlight was given toward student-centred approach. Digital game and problem-solving activities are an ideal combination of student-centred approach which facilitate active participation for students to practice and develop their thinking skills. This study was conducted to investigate the effect and the process of using digital game and problem-based learning skills to enhance higher order thinking skills in primary school student in the context of Malaysia. A preliminary study was conducted to 50 samples to collect data about their current higher order thinking skills level. The result shows samples are good in identify problem and solution, but weak in decision making and reasoning. To study the effect of digital game and problem-based learning combined in enhancing higher order thinking skills, a pre-test and post-test was conducted to 35 samples before and after three sessions of digital game problem-based learning section. After running a paired sample t test upon the pre-test and post-test, the result show that the combination of digital game and problem-based learning have significant effect in enhancing higher order thinking skills. To understand samples’ learning process, reflection journal was used after each learning section and an interview was conducted following the post-test. The data gathered indicate samples do enjoy learning with digital games and problem-based learning, and they agreed the approaches help them to learn better. However, they expected for more exciting games and group activities in the future. This study opens a gateway for developing student-centred and fun learning approach that beneficial toward student’s higher order thinking skills.